Permeable carbon fiber based thermoelectric film with exceptional EMI shielding performance and sensor capabilities - Junjie Zhu; Chuan Sun; Wanlin Feng; Mengran Chen; Peng-An Zong; Chunlei Wan (Journal of Advanced Ceramics, 2024)
Thermoelectric (TE) technologies offer a promising approach for directly converting skin heat into electricity for wearable electronics. Recognizing p-type Sb2Te3 and n-type Bi2Te3 as top-performing materials at room temperature, their rigid inorganic structure, with ultralow moisture permeability, poses challenges in warm and humid conditions, fostering bacterial growth and potential skin issues. To address this issue, we developed a cross-linked core−shell structure by electrodepositing Sb2Te3 (Bi2Te3) onto carbon fiber (CF). This architecture significantly improved the electrical conductivity and the Seebeck coefficient, resulting in a remarkable 300-fold increase in the power factor compared to that of pure CF. The CF/Sb2Te3 and CF/Bi2Te3 films demonstrated optimal power factors of 450 and 121 μW∙m−1∙K−2, respectively. Moreover, the fabricated films exhibited outstanding moisture permeability, over 3000 g∙m−2∙d−1, exceptional electromagnetic interference shielding efficiency approaching 93 dB, and versatility as sensors for language assistance and respiratory monitoring. These attributes underline their broad applicability, emphasizing their suitability for human health protection in diverse scenarios.